Performance Fatigability Is Not Regulated to A Peripheral Critical Threshold. Issue 4 (October 2018) - Thomas, Kevin; Goodall, Stuart; Howatson, Glyn
Abstract : The critical threshold hypothesis proposes that performance fatigability during high-intensity exercise is tightly regulated by negative-feedback signals from the active muscles. We propose that performance fatigability is simply dependent on the exercise mode and intensity; the consequent adjustments, in skeletal muscle and the other physiological systems that support exercise, interact to modulate fatigue and determine exercise tolerance. Abstract : The magnitude of performance fatigability observed after high-intensity exercise is task-dependent, and not regulated to a peripheral critical threshold.